DOENÇA DO ALZHEIMER NA TERCEIRA IDADE (REMUNOM, 2023)
Alzheimer's is a more frequent neurodegenerative pathology associated with age in our society, especially due to the aging of the population, it manifests itself slowly and progressively, through lapses in memory, attention, ability to make decisions, perform calculations, languages, visuospatial skills, and also psychiatric symptoms that end up compromising the individual's independence, analyzes in a simple way the need for specific care and the role of nurses in this process. Faced with the recognition of this reality, this study aims to analyze the impact that Alzheimer's disease has on the quality of life of an individual in old age and to describe what care nursing can offer to people with Alzheimer's disease in their third age. age in order to soften the impact suffered by the patient. Therefore, we opted to use a methodology of a qualitative nature in order to explain the subject in an explanatory way, through a bibliographical review. A review of important aspects associated with Alzheimer's disease was carried out, through a bibliographic survey on the subject. In the end, it was understood that the impacts of this disease do not affect only the elderly carrier, but also his family, and this, in most cases, does not have knowledge about the pathology, and consequently, does not know how to deal with the situation. In this way, it is considered that nursing care for the elderly affected by Alzheimer's disease is essential to improve their health status, thus promoting a better quality of life and autonomy, increasing their survival and strengthening their family and social life.